Gambaran Tingkat Stress pada Anggota Keluarga TBC di Lingkungan Kerja Puskesmas Ambulu Kab. Jember - Liria Rahmatika; Vito Satria Dwi Pratama; Lutfi Ariefianto (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
The stigma is wrong in the community that TB disease can not be cured so that the sufferer is ostracized by the surrounding community, one of them is the TB patient is difficult to get a job, Some even get laid off from their jobs because the person is diagnosed with a contagious disease. This raises many psychiatric problems with the consequent decline in labor productivity or human resources that can ultimately become a social burden for the family. Approximately 75% of TB patients are productive age group (15 - 50 years). The purpose of this study to determine the description of families whose members suffer from tuberculosis. Desain penelitian menggunakan deskriptif. The population in this study is all family members who have tuberculosis patients in Puskesmas Ambulu Kab. Jember as many as 96 respondents. The sample in this study were 54 respondents by using purposive sampling. Variables in this research is family stress level .. Data analysis using crosstab. Data collection using PSS-10 questionnaire with interview technique. The result of crosstab analysis showed that almost half of respondents had moderate stress level, 25 respondents (46%), had light stress level as many as 15 respondents (28%), heavy stress 14 respondents (26%). The incidence of stress is the relationship between the respondent and the patient, the number of sick relatives, and the length of treatment. The relation of the respondent to the patient shows that on average they are a member of the nuclear family. Knowledge and understanding of the danger of contracting pulmonary TB disease to other family members, becomes stressors (suppressors) against behavior that must be done by other family members. The inability of the family to perform its role in maintaining and maintaining a family member suffering from illness, will cause stress to other family members.